In Vitro Effects of Antagonistic Microorganisms on Fusarium oxysporum [Schlecht. Emend. Synd & Hans] Infecting Arachis hypogaea L. - B. Kannabiran*, P. Rajeswari and (Journal of Phytology, 2011)
InÃ‚Â anÃ‚Â attemptÃ‚Â to developÃ‚Â biocontrolÃ‚Â systemÃ‚Â forÃ‚Â managementÃ‚Â of Fusarium wilt in groundnut, Trichoderma viride, Trichoderma harzianum, and Pseudomonas fluorescens were evaluated for their antagonisticÃ‚Â activity againstÃ‚Â FusariumÃ‚Â oxysporum in vitro .The conidia of Fusarium oxysporumÃ‚Â were foundÃ‚Â toÃ‚Â be inhibited by all theÃ‚Â threeÃ‚Â antagonistic microorganisms. AmongÃ‚Â them,Ã‚Â highest percentÃ‚Â inhibition ofÃ‚Â conidialÃ‚Â germination was brought out Ã‚Â by Trichoderma viride [89.4%] followed by Trichoderma harzianum [85.7%] and Pseudomonas fluorescens [83.15%]and inhibition of radial mycelial growth were 86.6%, 84.0%,Ã‚Â 60.0% respectively.This inhibition is due to the volatile and non volatile metabolites and cell wall degrading enzymes produced by Trichoderma spp . AntagonisticÃ‚Â activity of PseudomonasÃ‚Â spp.against Fusarium oxysporum is mainly due to the antibiotics, Fe-chelating siderophores and hydrogen cyanide.